Expression of a Plastid-Targeted Flavodoxin Decreases Chloroplast Reactive Oxygen Species Accumulation and Delays Senescence in Aging Tobacco Leaves - Mayta, Martín L.; Lodeyro, Anabella F.; Guiamet, Juan J.; Tognetti, Vanesa B.; Melzer, Michael; Hajirezaei, Mohammad R.; Carrillo, Néstor (Frontiers in Plant Science, 2018)
Leaf senescence is a concerted physiological process involving controlled degradation of cellular structures and reallocation of breakdown products to other plant organs. It is accompanied by increased production of reactive oxygen species (ROS) that are proposed to signal cell death, although both the origin and the precise role of ROS in the execution of this developmental program are still poorly understood. To investigate the contribution of chloroplast-associated ROS to natural leaf senescence, we used tobacco plants expressing a plastid-targeted ﬂavodoxin, an electron shuttle flavoprotein present in prokaryotes and algae. When expressed in plants, flavodoxin specifically prevents ROS formation in chloroplasts during stress situations. Senescence symptoms were significantly mitigated in these transformants, with decreased accumulation of chloroplastic ROS and differential preservation of chlorophylls, carotenoids, protein contents, cell and chloroplast structures, membrane integrity and cell viability. Flavodoxin also improved maintenance of chlorophyll-protein complexes, photosynthetic electron flow, CO2 assimilation, central metabolic routes and levels of bioactive cytokinins and auxins in ageing leaves. Delayed induction of senescence-associated genes indicates that the entire genetic program of senescence was affected by flavodoxin. The results suggest that ROS generated in chloroplasts are involved in the regulation of natural leaf senescence.